PENERAPAN MODEL SAINS TECHNOLOGY AND SOCIETY UNTUK MENINGKATKAN SIKAP KEPEDULIAN DAN KREATIVITAS - Sari, Noca Yolanda; Pargito, Pargito; Darsono, Darsono (Jurnal Studi Sosial / Journal of Social Studies, 2013)
This research is aimed to improve concerning attitude and creativity through technology science model of geography lesson. This research is Classroom Action Research. In this research, the data was gotten in improving concerning attitude and creativity of student. The instrument which is used are observation sheets, observation of teacher worksheets, attitude observation, field records, and documentation. The result of research show that Science Technology Model and Society can improve concerning attitude and creativity of student. It was shown by average of concerning attitude and creativity of student percentage at cycles. At first cycle, the percentage of concerning attitude is 59% and students’ creativity is 54%. At second cycles, the percentage of concerning attitude improves to 72% and creativity is 66%. At third cycles, the percentage of concerning attitude improves to 79% and student creativity is 78%.Penelitian ini bertujuan untuk Meningkatkan Sikap Kepedulian dan Kreativitas Siswa dengan menggunakan model pembelajaran dalam pembelajaran geografi. Penelitian ini merupakan Penelitian Tindakan. Dalam penelitian ini data yang diperoleh adalah berupa peningkatan sikap kepedulian dan kreativitas siswa. Instrumen yang digunakan yaitu lembar observasi dan lembar pengamatan kinerja pendidik, pengamatan sikap, catatan lapangan dan dokumentasi. Hasil penelitian menunjukkan bahwa dengan menggunakan Model Sains Technology and Society dapat meningkatkan sikap kepedulian dan kreativitas siswa. Hal ini ditunjukkan dengan rata-rata persentase sikap kepedulian dan kreativitas siswa pada siklusnya. Siklus I persentase sikap kepedulian 59 % dan kreativitas siswa 54%. Pada siklus II persentase sikap kepedulian naik menjadi 72% dan kreativtas 66%. Begitu pula dengan siklus III, persentase sikap kepedulian naik menjadi 79% dan kreativitas siswa 78%.Kata kunci:  kreativitas siswa, model sains technology and society, sikap kepedulian